The Story of Amber and Essie Told Here in Poems and Pictures / by Vera B. Williams. - Williams, Vera B. (New York, 2001)
A series of poems tells how two sisters help each other deal with life while their mother is working and their father has been sent to jail.
Keywords: Sisters; Juvenile poetry; Children's poetry, American; Sisters; Poetry; American poetry